The Covid-19 pandemic in Pakistan: denial, managing uncertainty, public response, and retrospection - Sajjad, PF (2024)
The Covid-19 pandemic has had far-reaching consequences beyond health, affecting global social, political, and economic structures. Spanning March 2020 to July 2021, my field research explored pandemic responses in Pakistan. Using an array of research tools, including autoethnography, digital ethnography, and online and in-person semi-structured interviews involving 139 participants from the city of Lahore and the village of X in the outskirts of Multan, I examined responses of participants with a wide range of other occupations and socio-economic backgrounds as well as government officials and doctors and nurses, taking into account diverse temporalities.